Ética Ambiental: Estudio exploratorio de la percepción estudiantil universitaria - Ramírez Apud López, Tammara (Revista scientific, 2019)
The present work is an exploratory study, has as purpose to know the perception of the Environmental Ethics that university students have and their opinion about some current environmental issues. An instrument was elaborated with 13 questions, 11 were closed questions, to have specific data and other 2 open questions, to obtain previous knowledge and the perception of the students on different topics related to environmental ethics. In the results, five of the eleven closed questions are presented, and for the two open questions, only some answers were considered due to many numbers of students who participated in the study. A total of 337 students from different careers were randomly selected to answer the questionnaire. The analysis results for closed questions are presented in an average and for the open questions were considered comments that the students were mentioned, in order to know the perception of the students regarding the different topics. The results show the interest of students for the topics, as well as the possibility of identifying some areas of opportunity to work with the university students, environmental ethics issue and environmental education to begin contributing with the Objectives for Sustainable Development (ODS) and the 2030 Agenda.En el presente trabajo se muestra un estudio exploratorio, cuya finalidad es conocer la percepción de la Ética Ambiental de estudiantes universitarios, a través de la opinión que proporcionan acerca de algunas problemáticas ambientales contemporáneas. Se elaboró un cuestionario integrado por 13 preguntas, 11 cerradas, para tener datos específicos y 2 abiertas, para obtener los conocimientos previos de los estudiantes y con ello, la percepción sobre los diferentes temas relacionados con la ética ambiental. Para fines de esta investigación, se reportan los resultados de 5 de las 11 preguntas cerradas y las 2 preguntas abiertas. Fueron seleccionados de forma aleatoria un total de 337 estudiantes de diferentes licenciaturas para contestar el cuestionario. El análisis de resultados se presenta de forma porcentual en las preguntas cerradas y las preguntas abiertas mencionan los comentarios vertidos por los estudiantes respecto a las diferentes temáticas. Los resultados muestran el interés de los estudiantes y la preocupación por las temáticas propuestas, así como, la posibilidad de identificar algunas áreas de oportunidad para trabajar con los universitarios, la ética ambiental y la educación ambiental con la finalidad de comenzar a contribuir con los Objetivos para el Desarrollo Sostenible (ODS) y la Agenda 2030